2002
DOI: 10.1046/j.1365-2982.2002.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Low antroduodenal pressure gradients are responsible for gastric emptying of a low‐caloric liquid meal in humans

Abstract: The motor mechanisms responsible for transpyloric flow of gastric contents are still poorly understood. The aim of our study was to investigate the relationship between luminal pressures and gastric wall motion and between gastroduodenal pressure gradients and pressure waves, and ante- and retro-grade transpyloric flow. In eight healthy volunteers, intraluminal pressures were recorded from the antrum and proximal duodenum. Transpyloric flow was monitored simultaneously using duplex ultrasonography, before, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
54
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 30 publications
9
54
0
1
Order By: Relevance
“…From a mechanical perspective, the stomach is a mixer, a grinder, a storage chamber and a sophisticated pump that controls the release of aqueous, lipid and solid gastric content into the duodenum (Meyer et al 1994). Whereas many studies have concentrated on gastric motility in emptying (Schwizer et al 1992;Gilja et al 1997;Hausken et al 2002), we focus here on the role of gastric motility in the breakdown of solid particles and mixing of gastric content. We study details of gastric mixing by the coordination of specific patterns of antral contraction with temporal changes in gastric wall motion and pyloric opening, using computer simulations of the human stomach in the fed state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a mechanical perspective, the stomach is a mixer, a grinder, a storage chamber and a sophisticated pump that controls the release of aqueous, lipid and solid gastric content into the duodenum (Meyer et al 1994). Whereas many studies have concentrated on gastric motility in emptying (Schwizer et al 1992;Gilja et al 1997;Hausken et al 2002), we focus here on the role of gastric motility in the breakdown of solid particles and mixing of gastric content. We study details of gastric mixing by the coordination of specific patterns of antral contraction with temporal changes in gastric wall motion and pyloric opening, using computer simulations of the human stomach in the fed state.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations can resolve pressure variations that are within the noise of manometric data, suggesting that manometry captures primarily higher pressures associated with direct luminal contact. Whereas Hausken et al (2002) report transpyloric pressure differences during emptying in the range 2-20 mmHg, Indireshkumar et al (2000) used high-resolution manometry and conditional statistics to measure mean transpyloric pressure difference of only 0.3 mmHg over 1 cm during antral quiescence and pyloric relaxation. Our computer simulations are consistent with the latter result and suggest that pressure differences of order several mmHg are likely to be a result of direct lumen-occluding contractions over the manometric sidehole.…”
mentioning
confidence: 99%
“…Studies using antroduodenal manometry and concurrent duplex ultrasonography [11,12] or magnetic resonance imaging (MRI) [10] have suggested that the ''pressure-pump'' mechanism is important in the gastric emptying of fluids.…”
Section: Introductionmentioning
confidence: 99%
“…The critical factors that control gastric emptying are gastric tone, antral peristalsis, pyloric resistance, and duodenal feedback control. Dysfunction of any of these factors results in impairment of gastric emptying (13,19,22,24,25,27,36,38,45,47,48). Effective peristaltic antral contractions play a major role in solid gastric emptying (13,27).…”
mentioning
confidence: 99%